An update on the management of cholestatic liver diseases - Appanna, Gautham (Clin Med (Lond), 2020)
Cholestatic liver diseases are a challenging spectrum of conditions arising from damage to bile ducts, leading to build-up of bile acids and inflammatory processes that cause injury to cholangiocytes and hepatocytes. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are the two most common cholestatic disorders. In this review we detail the latest guidelines for the diagnosis and management of patients with these two conditions.